Can the Methotrexate Therapy Prevent the Development of Uveitis in Patients with Juvenile Idiopathic Arthritis: Results of a Retrospective Study - M. M. Kostik; E. V. Gaydar; M. F. Dubko; V. V. Masalova; L. S. Snegireva; I. A. Chikova; E. A. Isupova; T. N. Nikitina; E. D. Serogodskaya; O. V. Kalashnikova; A. Ravelli; V. G. Chasnyk ("Paediatrician" Publishers LLC, 2015)
Background: Uveitis is one of the most common extra-articular manifestations of juvenile idiopathic arthritis (JIA). Currently, the possibility of reducing the risk of uveitis in children with JIA by using methotrexate has been studied.Objective: Our aim was to analyze the results of treatment of children with JIA by studying the relation between the use of methotrexate and the risk of uveitis.Methods: A retrospective uncontrolled study. The case histories of patients with JIA who were treated for at least 2 years after the onset of the disease were studied. The results of treatment of patients who received and who did not receive methotrexate were studied (standard therapy - non-steroidal anti-inflammatory drugs and intra-articular injections of glucocorticoids). The established cases of uveitis were taken into account.Results: The study analyzed the results of observation of 281 children with JIA. In the methotrexate group, uveitis was detected in 22/191 (11.5%), and in the control group - in 42/90 (46.7%) of patients (OR 6.7; 95% CI 3.7-12.3). The time period between the onset of JIA and development of uveitis in two groups under study was the same and equal to 24 (12; 67) and 17 months (7; 35), respectively (p = 0.232). Multivariate regression analysis showed that the main predictors of uveitis were oligoarticular course of JIA (HR = 1.89), positive antinuclear antibody test (HR = 2.14), onset of JIA under the age of 5 (HR = 2.56), female gender (HR = 1.82),and the absence of methotrexate in the therapy (HR = 0.24).Conclusion: The treatment with methotrexate may reduce the risk of uveitis in patients with JIA. To confirm this hypothesis, randomized studies are needed.